PENGARUH CAPITAL ADEQUACY RATIO, RISK PROFILE DAN BEBAN OPERASIONAL PENDAPATAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN - Hartini, Hartini; Yusran, Rio Rahmat (Aksara Public, 2020)
This study aims to analyze effect of capital adequacy ratio, risk profile and operation expenses for operating income on return on equity of bank registered at Indonesia Financial Authority for 2014-2018. Risk profile divided into financing to deposit ratio and non performing financing. Analyze used is multiple linear regression, classic assumption test, t-test, f-test and coefficient of determination test. Total population are 52 banks, using purposive sampling techniques, samples are 24 banks. Result of t-test are capital adequacy ratio affect to return on equity by t-arithmetic -5,885>t-table 1,658 with significance value of 0,000>0,05, financing to deposit ratio affect to return on equity by t-arithmetic -2,320>t-table 1,658 with significance value 0,022<0,05, non performing financing affect to return on equity by t-arithmetic -2,405>t-table 1,658 with significance value 0,018<0,05 and operation expenses operation income by t-arithmetic-13,697>t-table 1,658 with significance value 0,000> 0,05. F test’s result of capital adequacy ratio, financing to deposit ratio, non performing financing and operation expenses operating income influence return on equity calculated on F value 64,090>F table 2,450. Result on coefficient of determination test shows independent variable influences 69% affect return on equity, and 31% is influenced by other variables no included in this research.